Treatment of arterial hypertension in older adult patients in primary care: is there risk with the medication? - Vargas Ponce, Kenneth Grenis (2016)
Mr. Editor: Hypertension (HTA) is a public health problem worldwide, with complications of lethality and its prevalence is 30% to 45% in the general population (1). It is one of the leading causes of consultation in primary care and its prevalence increases with age, affecting 48% of people over 60 years according to studies of blood pressure in Spanish population in primary care centers (PRESCAP) (2 ).